2016
DOI: 10.1039/c5gc01558h
|View full text |Cite
|
Sign up to set email alerts
|

Towards multi-purpose biorefinery platforms for the valorisation of red grape pomace: production of polyphenols, volatile fatty acids, polyhydroxyalkanoates and biogas

Abstract: The development of a multi-purpose four step-cascading biorefinery scheme for the valorization of red grape pomace (GP) was proposed. The consecutive processes were respectively dedicated to (a) the recovery of polyphenols by supercritical CO2 extraction, (b) the production of volatile fatty acids (VFAs) by anaerobic acidogenic digestion, (c) the exploitation of produced VFAs as the precursors for the biotechnological production of polyhydroxyalkanoates (PHAs) and (d) the production of a CH4-rich biogas by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 54 publications
1
73
0
1
Order By: Relevance
“…Many studies reported the utilization of wine lees for the production of various commercial products, such as ethanol, tartaric acid and phenolic compounds . Wine lees have also been proposed as nutrient supplements in several fermentation processes, including lactic acid, xylitol and PHAs production …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported the utilization of wine lees for the production of various commercial products, such as ethanol, tartaric acid and phenolic compounds . Wine lees have also been proposed as nutrient supplements in several fermentation processes, including lactic acid, xylitol and PHAs production …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Wine lees have also been proposed as nutrient supplements in several fermentation processes, including lactic acid, xylitol and PHAs production. [6][7][8][9] The worldwide annual production capacity of cheese whey could be estimated at about 160 million t. 10 Cheese whey retains most of the milk lactose (39-60 g L −1 ) as well as proteins (1.4-33.5 g L −1 ), fats (0.99-10.58 g L −1 ), and mineral salts (0.46-10%) among others. 11 Many studies have focused on the recovery of value-added components from cheese whey (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, grape waste represents a good source of vitamins, minerals, lipids, proteins, carbohydrates and polyphenolic compounds (especially phenolic acids, ellagitannins, flavonols, flavan-3-ols such as catechins and their isomers, anthocyanins, pro-anthocyanidins and the stilbene derivative, resveratrol) (Nowshehri et al, 2015). Grape wastes are not considered hazardous waste, but in large amounts they can contribute to the pollution, due to the high chemical and biological oxygen demand (Martinez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of natural sources of grape phenolics, innovative methods for the purification of polyphenols from grape pomace have been proposed (e.g. by supercritical CO 2 extraction), although such methods require long process and expensive technologies . For these reasons, there is interest in assessing the effect of grape pomace from industry by‐products without purification or extraction of the sole polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…by supercritical CO 2 extraction), although such methods require long process and expensive technologies. 24 For these reasons, there is interest in assessing the effect of grape pomace from industry by-products without purification or extraction of the sole polyphenols. The use of such extract was recently reported by Sanz-Buenhombre et al 25 who used in vitro gastrointestinal digestion to assess the bioavailability of polyphenols from grape extract and polyphenol degradation during the simulated digestion.…”
Section: Introductionmentioning
confidence: 99%